External root resorption (EARR) and interleukin-1β (rs1143634) gene polymorphism in the Bataknese population: a pilot study - Bahirrah, Siti; Lestari, Widya; Zulhakim, Amir; Suwandi, Asrul; Irfan, Nining Irfanita (AIP Publishing, 2023)
External apical root resorption (EARR) is a condition that frequently arises after orthodontic treatment. Interleukin 1 (IL-1) is the gene responsible for the initiation of bone resorption and activating the osteoclasts, and is responsible for the potential of root resorption development. This study investigated the presence of a single nucleotide polymorphism (rs1143634) in IL-1β gene and its relationship with root resorption in 20 individuals of Bataknese background. Panoramic radiographs of all patients were taken before and after orthodontic treatment. Subjects were classified as either EARR ≥2mm or EARR <2mm based on their permanent central maxillary incisor measurements. Unstimulated saliva samples were taken for genetic screening. The polymorphism was analyzed by the polymerase chain reaction followed by purification and sequencing method. For male subjects, 2 subjects fell under Grade 0, while Grades I, II and III recorded 3 subjects. Meanwhile for female subjects, 7 fell under Grade II, followed by 5 under Grade I, 2 under Grade 0, and 1 patient under Grade II. Following sequencing method, there is no polymorphism detected in all samples. The current study shows that single nucleotide polymorphism (rs1143634) in IL-1β has no role in predisposition towards EARR in the Bataknese population. However, based on the data, we recommend further studies in larger sample populations for better accuracy and consistency.